2014
DOI: 10.1111/eos.12164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of methyl mercaptan on the repair bond strength of composites fabricated using self‐etch adhesives

Abstract: The influence of methyl mercaptan on the repair bond strength of composites fabricated using self-etch adhesives was investigated. The surface free-energies were determined by measuring the contact angles of test liquids placed on composites that had been immersed in different concentrations of methyl mercaptan (0.01, 0.1, and 1.0 M). To determine the repair bond strength, self-etch adhesives were applied to the aged composite, and then newly added composites were condensed. Ten samples of each specimen were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…86 Adeziv sistemlerden ise self etch sistemler kullanıldığında tamirde en yüksek bağlanma dayanımı elde edilmiştir. 87 Tamir sonucu elde edilen bağlanma dayanımının 18 MPa'dan fazla olması istenmektedir. 88 Literatürde kompozit rezin tamirinde silan ve self etch adezivlerin kullanılmamasını öneren çalışmalar da mevcuttur.…”
Section: • Adeziv Sistem Ve Kompozit Uygulama Yöntemiunclassified
“…86 Adeziv sistemlerden ise self etch sistemler kullanıldığında tamirde en yüksek bağlanma dayanımı elde edilmiştir. 87 Tamir sonucu elde edilen bağlanma dayanımının 18 MPa'dan fazla olması istenmektedir. 88 Literatürde kompozit rezin tamirinde silan ve self etch adezivlerin kullanılmamasını öneren çalışmalar da mevcuttur.…”
Section: • Adeziv Sistem Ve Kompozit Uygulama Yöntemiunclassified
“…We decided each sample size (n=6) with calculation module (Open epi, http://www.openepi.com/Menu/OE_Menu.ht) under the condition of 95% confidence interval and 90% power. The contact angle (θ), was measured from drop images using image analysis software (ImageJ, NIH, Bethesda, ML), and the SFE was obtained by the following equations 7) . The Young-Dupré equation:…”
Section: Contact Angle Measurements and Sfe Calculationsmentioning
confidence: 99%
“…Marshall et al 1) found that cohesion between similar molecules/atoms affects intermolecular attractions, and Combe et al 2) stated that knowledge of the reactivity or energy of surfaces, and in particular their interaction with fluids, was very important. Assessment of surface energy has been used to analyze the surface properties of medical biomaterials; such as intraocular lenses 3) , drug tablets 4) and orthopedic implants 5) , and also to analyze cell adhesion to dental implants 6) , resin adhesion to tooth crown restorations 7) and dentures 2,8) , as well as tooth substance adhesion to enamel 9) and dentin 10) . The occurrence of surface bonds can be investigated by analyzing transitions of surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kanzow and Wiegand's retrospective study indicated that among repaired restorations, the rate of failure of the repaired part was still higher than that of the remaining parts of the original restoration (Kanzow and Wiegand, 2020). It has also been widely investigated inin vitro studies that an increase in roughness of the aged composite surface through etching, air abrasion, polishing, and laser irradiation results in a considerable improvement in the bond strength (Barcellos et al, 2015;Valente et al, 2015;Yokokawa et al, 2015;Pilo et al, 2016;Nagano et al, 2018;Flury et al, 2019;Kanzow et al, 2019;Martos et al, 2019). Brosh et al indicated that the repair bond between the original and newly added resin composite could be influenced by chemical and mechanical mechanisms: reaction with the surface resin matrix and exposed inorganic fillers could account for chemical bonding and macro/micromechanical attachment could account for mechanical bonding (Loomans et al, 2011;Pilo et al, 2016), when we repair the aged resin composites that had defects, such as fracture defects, discolouration, treatments are needed to create a surface for better adhesive between aged composite substrate and newly added composite.…”
Section: Introductionmentioning
confidence: 99%